Review of the IMF's Trade Restrictiveness Index. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines the construction of the index and its use over the past seven years, identifies its limitations, examines several alternative measures of trade policy, and highlights some options for improving the Fund's use of trade policy indicators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet